1982
DOI: 10.1161/01.hyp.4.6.764
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive action of captopril in spontaneously hypertensive and normotensive rats. Interference with neurogenic vasoconstriction.

Abstract: The effects of captopril and angiotensin II on adrenergic neurotransmission have been studied in spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY). In a pithed rat preparation, vasoconstrictor responses evoked by spinal stimulation were greater in SHR than WKY (p < 0.01). Captopril reduced responses to electrical stimulation and this reduction was greater in the SHR (p < 0.001). Bilateral nephrectomy reduced the vasoconstrictor responses to nerve stimulation in both strains of rat and abolished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 29 publications
4
18
0
1
Order By: Relevance
“…Intracerebroventricular injections of renin-angiotensin system antagonists decrease blood pressure in spontaneously hypertensive and normotensive rats (9,17,19,20,32,33). We also confirmed that captopril, an angiotensin-converting enzyme inhibitor, decreases blood pressure in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 74%
“…Intracerebroventricular injections of renin-angiotensin system antagonists decrease blood pressure in spontaneously hypertensive and normotensive rats (9,17,19,20,32,33). We also confirmed that captopril, an angiotensin-converting enzyme inhibitor, decreases blood pressure in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 74%
“…Pressor responses to NA in SHR are similar to those of control rats, but neurogenic vasoconstrictor responses are greater in SHR. 12 Interestingly, ACE inhibition produces a greater attenuation of nerve stimulated responses in SHR compared to control. 12 Acutely, inhibition of AII formation may alter the release of sympathetic neurotransmitters or may have a direct action on effector cell-responsiveness.…”
Section: Discussionmentioning
confidence: 98%
“…12 Interestingly, ACE inhibition produces a greater attenuation of nerve stimulated responses in SHR compared to control. 12 Acutely, inhibition of AII formation may alter the release of sympathetic neurotransmitters or may have a direct action on effector cell-responsiveness. [3][4][5][6] With chronic ACE inhibition transmitter synthesis may be altered or other actions resulting in structural changes in the vasculature may occur.…”
Section: Discussionmentioning
confidence: 98%
“…32 Increased Ang II levels within the vascular wall could influence vascular growth, either by direct effects on vascular smooth muscle as discussed above or indirectly by potentiation of sympathetic activity. 33 - 34 Norepinephrine and epinephrine have been shown to increase the growth rate of cultured vascular SMCs, 35 and the sympathetic nervous system has a role in vascular SMC growth in hypertension. 36 The blockade of Ang II formation by captopril in SHR has an effect on the vascular wall over and above that predicted by its blood pressure-lowering effect.…”
mentioning
confidence: 99%